2020
DOI: 10.1111/aogs.13978
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fms‐like tyrosine kinase to placental growth factor ratio in different stages of early‐onset fetal growth restriction and small for gestational age

Abstract: Introduction Increased soluble fms‐like tyrosine kinase to placental growth factor ratio (sFlt‐1/PlGF) has been demonstrated in early‐onset fetal growth restriction (FGR) and small for gestational age (SGA). sFlt‐1/PlGF cut‐offs have been described to assess preeclampsia severity; however, sFlt‐1/PlGF values present in early‐onset SGA and different FGR severity stages remain unknown. Hence, the objective of this study was to describe and compare the sFlt‐1/PlGF values and pregnancy outcomes among early‐onset S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The authors found significant correlation between greater sFlt-1/PlGF ratio values and gestational age at delivery, time from diagnosis to delivery, birthweight z-scores, and time in NICU (r = −0.637, r = −0.576, r = −0.161, and r = 0.311, respectively). Therefore, they concluded that sFlt-1/PlGF could aid in early-onset FGR/SGA severity classification and clinical management when Doppler assessment is not feasible [16]. In our study sFlt-1/PlGF ratio was significantly related to birthweight and NICU hospitalization as well.…”
Section: Discussionsupporting
confidence: 53%
“…The authors found significant correlation between greater sFlt-1/PlGF ratio values and gestational age at delivery, time from diagnosis to delivery, birthweight z-scores, and time in NICU (r = −0.637, r = −0.576, r = −0.161, and r = 0.311, respectively). Therefore, they concluded that sFlt-1/PlGF could aid in early-onset FGR/SGA severity classification and clinical management when Doppler assessment is not feasible [16]. In our study sFlt-1/PlGF ratio was significantly related to birthweight and NICU hospitalization as well.…”
Section: Discussionsupporting
confidence: 53%
“…Overexpression of sFlt-1, either naturally or caused by experimental mutant adenoviral injection in preeclamptic pregnant models, has been shown to be associated with hypertension, glomerular endotheliosis, delivery of growth-restricted offspring, and fetoplacental Doppler abnormalities. [24][25][26] Accordingly, in our study, sFlt-1 was elevated in severe PE compared to normal pregnant women and was more prominently elevated in those with composite adverse maternal outcomes. In addition, we demonstrated a correlation between sFlt-1 and fullPIERS scores, a previously validated model in our institution that was used to predict adverse maternal outcomes in PE.…”
Section: Discussionsupporting
confidence: 51%
“…There are reports that preeclampsia is linked to longer hospitalizations of neonates in the neonatal intensive care units (NICU) [ 19 ]. Other authors have shown that a longer stay in the neonatal care unit may be related to an elevated sFlt-1/PlGF ratio or to an increased sFlt concentration or a decreased PlGF content alone [ 30 , 31 ]. In our study, the sFlt-1/PlGF ratio demonstrated similar correlations, with the neonates born to mothers with higher ratios spending more time in hospital.…”
Section: Discussionmentioning
confidence: 99%